Increasing The Students’ Ability In Reading Comprehension By Using Shared Reading Strategy At The Eighth Grade Of SMP Negeri 3 Gunungsitoli In 2022/2023 - Silvyn Jernih Lase; Adieli Laoli; Elwin Piarawan Zebua; Yasminar Amaerita Telaumbanua (Departement of Mathematics Education, 2024)
Reading was a part of four skills in mastering English that should be taught at school because it an important skill to be mastered. In learning English there were four basic skills that should be mastered by students. They were listening, speaking, reading and writing. Reading had to be mastered by students because it could help students got a lot of information and could increase their knowledge for example by reading; the students were expected to build their own comprehension of the text. Based on the observation that was done by researcher in SMP Negeri 3 Gunungsitoli, especially in the eighth grade, most of the students could not achieve the MCC 70. Problems faced by students in learning reading comprehension: the students lacked of vocabulary, the students were not able to identified the topic of the recount text, the students lacked an understanding of the meaning of words in the text, the students could not know the generic structure of the recount text. The research did aim to address students’ problems in reading comprehension through shared reading strategy. This research used a quantitative method and used Classroom Action Research (CAR) design which consists of planning, action, observation, reflection. This research was carried out two cycles and each cycle was conducted two meetings. In cycle I showed that there were 20 students who did not pass the MCC out of 30 students and the average student score was 51.66. In addition, in Cycle I there were results from student evaluations with the lowest score of 20 and the highest score of 85. In Cycle II, all students had passed the MCC out of 30 students and with an average student score of 85.16 and there was a lowest score of 70 and the highest score of 100. Based on the results of the study, the researcher concluded that the used of shared reading strategy could improve students’ reading comprehension skill.